Hypersensitivity diseases: type II-IV hypersensitivity - Marshall, Sara (Henry Stewart Talks, 2021)
Hypersensitivity reactions, Classifying hypersensitivity disorders, Immunological mechanisms of hypersensitivity disorders, Components of the immune system and hypersensitivity reactions, Management of hypersensitivity